An Efficient Decision making in Crop cultivation using Soft Set Theory - Mohanambal, S; Jeyanthi, G; Pethalakshmi, A (International Journal of Computer Sciences and Engineering, 2025)
India is associate agricultural country and majority of its population is engaged in agricultural works and farming outcomes being their own supply of financial gain. Agriculture sector faces several challenges of enhancing production with accessible natural resources. Soft set theory plays an important role to show great ability in decision making model like crop selection, crop planning, irrigation planning, water resource management etc. Even if a near optimal solution is obtained, it will have a very large impact. This can be achieved by the use of soft set techniques. This paper brings in awareness on decision making model in crop cultivation by using soft set theory that helps to identify the crop to be cultivated by a farmer which suits best of his expectations by the questionnaire and it can be optimized by various statistical measures.